METODE NEWTON-STEFFENSEN DENGAN ORDE KEKONVERGENAN TIGA UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR - Fitriani '; Johannes Kho; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses Newton-Steffensen method to solve a nonlinear equation. The method is obtained by combining Newton's method with Steffensen's method. The proposed method has third order convergence. Computational examples illustrate that the discussed method is better than Newton method and Steffensen method in terms of obtaining the root for same initial guesses.